PSYCHOLOGICAL WELL-BEING PADA PENGIDAP TALASEMIA MAYOR - Ade Ayu Amanda; Agus Sukirno; Peni Ramanda (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2026)
This study aims to understand the psychological well-being of individuals with thalassemia major from the perspective of Islamic Guidance and Counseling. This topic is important to study because individuals with thalassemia major must undergo regular blood transfusions and face various physical, psychological, and social challenges that have the potential to affect their quality of life. This study is based on the assumption that individuals with thalassemia major can still build psychological well-being through the process of self-adaptation, social support, and the reinforcement of religious values in their lives. The study employs a qualitative approach using the phenomenological method to understand the subjective experiences of individuals living with major thalassemia. Data were collected through in-depth interviews with three informants living with major thalassemia and analyzed based on the dimensions of psychological well-being proposed by Carol D. Ryff. The results indicate that the informants were able to develop psychological well-being through self-acceptance of their health condition, supportive social relationships, autonomy in decision-making, the ability to manage daily activities, having a sense of purpose, and experiencing personal growth reinforced by religiosity and family support. These findings indicate that the integration of social support and spiritual values plays a significant role in fostering the psychological well-being of individuals with thalassemia major, thereby offering implications for the development of Islamic guidance and counseling services for individuals with chronic illnesses.